Pengaruh Kebijakan Otonomi Khusus Papua Terhadap Pembangunan Prasarana Pendidikan dan Kesehatan di Kabupaten Manokwari Selatan, Provinsi Papua Barat - Kadam, Andarias; Setiadi, Rukuh (Universitas Diponegoro, Indonesia, 2021)
This research is a descriptive study combining qualitative and quantitative approach. It compares infrastructure development before and during the special autonomy era. The main focus of this research is the special autonomy policy for education and health development in South Manokwari Regency. This study discusses